Experiences with carbenicillin in the treatment of septicaemia and meningitis - Richardson, A. E. (1968)
Experiences in the use of carbenicillin, a new penicillin active against Pseudomonas aeruginosa and other Gram-negative bacteria in the treatment of septicaemia and meningitis are described. Blood levels of carbenicillin in excess of the levels required to inhibit the infecting organisms were obtained using intravenous infusions of large doses together with probenecid by mouth. High cerebrospinal fluid levels of carbenicillin were ensured in the meningitis patients with daily intrathecal or intraventricular injections. Carbenicillin undoubtedly controlled the course of Ps. aeruginosa septicaemia in two patients. Rapid sterilization of the cerebrospinal fluid was achieved in both meningitis patients with clinical improvement. No evidence of toxicity was seen and daily intrathecal injections were well tolerated.